Defect-Promoted Ni-Based Layer Double Hydroxides with Enhanced Deprotonation Capability for Efficient Biomass Electrooxidation - Yang, Yuwei (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.